Innovative approaches in precision radiation oncology: advanced imaging technologies and challenges which shape the future of radiation therapy - Yan, Yue; Alexander, Daniel A.; Bednarz, Bryan P.; Bronk, Lawrence F.; Chen, Huixiao; Gladstone, David J.; Han, Bin; Iannuzzi, Christopher M.; Li, Yuting; Nguyen, Ngoc; Mulenga, Natasha; Viscariello, Natalie N.; et al. (Frontiers in Medicine, 2025)
Radiation oncology is undergoing a transformative shift toward precision medicine through unprecedented advances in imaging technologies that enable increasingly personalized and adaptive cancer treatment. This comprehensive review synthesizes the underlying physical principles, current clinical applications, technical challenges, and quality assurance requirements across the complete spectrum of emerging imaging-guided radiation therapy approaches. We examine magnetic resonance-guided radiotherapy systems that enable daily soft-tissue visualization and online plan adaptation, positron emission tomography-guided platforms that allow real-time tracking of metabolically active tumor regions, advanced cone beam computed tomography systems supporting rapid adaptive workflows through artificial intelligence-enhanced image generation, and novel applications including Cherenkov radiation imaging and stereoscopic guidance with surface tracking. For proton therapy, we address innovations spanning dual-energy computed tomography, proton computed tomography, and in-vivo range verification that tackle fundamental range uncertainty limitations. In theranostics, we explore sophisticated quantitative imaging for personalized radiopharmaceutical dosimetry. Our analysis reveals that while these technologies converge to enable increasingly adaptive and biology-informed dose delivery, realizing their full clinical potential requires rigorous multicenter validation, standardized quality assurance protocols, integration of multi-omics with functional imaging, trustworthy automation with continuous performance monitoring, interoperable data pipelines, enhanced workforce training, and attention to equitable access across diverse patient populations. This integrated perspective provides a forward-looking framework to guide clinicians, medical physicists, and researchers in navigating the rapidly evolving landscape of precision radiotherapy while ensuring safe and effective implementation of these transformative technologies.